Kajian Karakteristik dan Potensi Sumberdaya Lahan Untuk Perencanaan Pembangunan Pertanian di Kabupaten Merangin Berdasarkan Zona Agro Ekologi (ZAE) - Hendri Purnama; Jon Hendri; Busyra Buyung Saidi (Seminar Nasional Lahan Suboptimal, 2019)
Purnama H, Hendri J, Saidi BB. 2019. Characteristics of potential land resources for agricultural planning in merangin district based on Agroecological Zones (ZAE).  In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang  4-5 September 2019. pp. 270-276. Palembang: Unsri Press. The study of Characteristics and Potential of Land Resources in Merangin Regency aims to identify the potential of land resources for agricultural development, to develop information on the type of land use for the right agricultural system as a basis for sustainable agricultural development, and to develop maps of zoning of agricultural commodities based on ZAE scale of 1: 50,000. The study was conducted with a desk study approach, soil sampling and surveys. The results of the study found that the climate classification of Merangin district was included in type B. The Merangin district landform consisted of 134 land units. SPT 1 to 6 are soil in the alluvial group, soil types Tropaquepts, Dystropepts and Tropofluvents. SPT 7 is soil in the peat group (freshwater oligotrophic peat dome), the parent material of peat. SPT 8 is soil in the Karst group, limestone mother material, soil type Inceptisol (Eutroppepts). SPT 9 to 81 are soil in the tectonic/structural group, andesite tuff parent material, ultisol and inceptisol soil types. SPT 82 to 133 is the soil in the volcanic group, the parent material of tuff andesite, the soil type consists of inceptis ol, oxisol, and ultisol. Based on the agroecological zone, Merangin Regency consists of 6 (six) zones and 9 (nine) sub zones. Food and horticultural agricultural development areas are in zones III and IV namely Zone III/Dfksvei-1 and III/ Dfksvei-2, Zone IV/Dfksvei-1 and IV/Dfksvei-1 covering 303,429 ha (40,827%), commodity development areas estate crops and horticulture, namely in zone II/Dfksvei-1 and II/Dfksvei-2 covering 62,596 ha (8,422 ha), the estate crop estate is in zone V/ Dfksvei with 1,767 ha (0.24%). And the conservation area is zone I/Dfxvei with an area of 37,417 ha (5.03%) of the area of Merangin district.Keywords: agroecological zones, commodity zoning, land resources, land suitability, Merangin